(untitled) (Cadernos de Sociomuseologia, 2026)
This article examines the previously overlooked role of the International Movement for a New Museology (MINOM) in helping to conceive the Him Dak Eco-museum, the first and only official ecomuseum within U.S. territory, established by the Ak-Chin Indian Community in Arizona. Building upon a chronology gap identified by Ana Mercedes Stoffel Fernandes in her foundational work on the MINOM, the study poses the central question: To what extent was MINOM involved in the founding of the Him Dak Eco-museum? The study employs a qualitative, historiographical methodology, relying on archival research, bibliographic review, and interviews with key figures involved in the ecomuseum’s conception. Despite limitations in accessing direct testimony from Ak-Chin community members, the research reconstructs a timeline of events between 1985 and 1990 that demonstrates the presence and influence of MINOM members in the museum’s conceptual and educational development phase of the ecomuseum. The findings reveal that while MINOM’s influence was indirect and informal, it nonetheless shaped the trajectory of the Him Dak’s early conception phases through key meetings and other events. Furthermore, the article highlights how the Him Dak Eco-museum serves as a case study of the "underground results" of MINOM—initiatives that fall outside its formal historiography but embody the Movement’s values. Finally, the article critiques the exclusionary tendencies within MINOM’s own historiographical canon, calling for a broader, more inclusive recognition of community-led museological practices inspired by New Museology principles. Keywords: International Movement for a New Museology (MINOM); New Museology; Ecomuseum; Sociomuseology; Ak-Chin Indian Community